Short-term survival after colorectal cancer in a screened versus unscreened population. Issue 5 (July 2019) - Syse, Astri; Soneji, Samir S.; Andrew, Angeline S.; Tretli, Steinar; Baili, Paolo; Bynum, Julie P.W.
Aims: United States' (US) colorectal cancer (CRC) screening and treatment practices seek to reduce mortality. We examined the survival of US patients compared with patients in the virtually unscreened Norwegian population. Methods: We compared short-term survival after CRC between the US and Norway using relative survival (RS) and excess mortality (EMR) analyses. The CRC patients were aged 50 and older diagnosed in the US (Surveillance, Epidemiology and End Results registry, 2004, N=9511) and in Norway (Cancer Registry of Norway, 2003–2005, N=8256). Results: Death occurred within three years for 39% of the CRC patients. Stage distributions were more favorable for US patients. Stage-specific survival was similar for localized and regional cancers, but more favorable for US distant cancers. In multivariate models of patient, tumor and treatment characteristics, patients (especially below age 80) in the US experienced longer survival (EMR 0.9, CI 0.8–0.9). Stage-specific analyses showed, however, that survival for localized cancers was relatively shorter in the US than in Norway (EMR 1.4, CI 1.1–1.8), but longer for distant cancers (EMR 0.8, CI 0.7–0.8). Conclusions: The enhanced survival for US CRC patients likely reflects a screening-related earlier diagnostic stage distribution, as well as prioritized life extension for patients with metastatic cancers, reflecting vastly different health care systems in the two countries. CRC screening is currently under consideration in Norway. For survival outcomes, the current findings do not discourage such an implementation. Other screening-related aspects such as feasibility and cost-benefit are, however, also relevant and warrant further research within a socialized health system.